Developmental Origins of Pregnancy-Related Morbidity and Mortality in Black U.S. Women - Lin, Betty; Appleton, Allison A. (Frontiers in Public Health, 2022)
In the US, Black women are at disproportionate risk for pregnancy-related morbidity and mortality (PRMM). Disparities in PRMM have been tied to elevated rates of obstetric cardiometabolic complications for Black women. Research seeking to elucidate the determinants of Black PRMM to date have focused predominantly on risk factors occurring during pregnancy (e.g., health risk behaviors, quantity and quality of prenatal care, provider behaviors, and attitudes). Meanwhile, other research investigating the developmental origins of health and disease (DOHaD) model indicates that the origins of adult cardiometabolic health can be traced back to stress exposures occurring during the intrauterine and early life periods. Despite the relevancy of this work to Black PRMM, the DOHaD model has never been applied to investigate the determinants of Black PRMM. We argue that the DOHaD model represents a compelling theoretical framework from which to conceptualize factors that drive racial disparities PRMM. Research and intervention working from a developmental origins orientation may help address this urgent public health crisis of Black PRMM.